Pemphigoid - diagnosis and treatment. Polish Dermatological Society Consensus - Katarzyna Woźniak; Marian Dmochowski; Waldemar Placek; Elżbieta Waszczykowska; Agnieszka Żebrowska; Roman Nowicki; Iwona Flisiak; Rafał Czajkowski; Jacek Szepietowski; Joanna Maj; Andrzej Kaszuba; Ligia Brzezińska-Wcisło; et al. (Termedia Publishing House, 2016)
Bullous pemphigoid (BP) is an autoimmune subepidermal blistering disease affecting elderly people, more than 65 years old. Patients aged over 80 are the main group of interest. The incidence of BP has been significantly increasing for the last 15 years in the whole of Europe. The diagnosis of BP is established on the basis of typical clinical features and in vivo bound IgG/C3 along the basement membrane zone, whereas characterization of target antigens for circulating antibodies may be established using tests containing BP antigens, i.e. ELISA test with recombinant NC16a domain of BP180 antigen and BIOCHIP. The goal of therapy of BP is to inhibit development of new lesions, healing the older ones and elimination of pruritus. At present only monotherapy with 0.05% clobetasol propionate cream used topically on the whole body has been proved to be the best for BP patients. Alternative therapies include methotrexate and the combination of tetracycline and nicotinamide. Prednisone, especially in doses higher than 0.5 mg per body weight daily, should be avoided in old patients with comorbidities such as diabetes, hypertension, stroke or osteoporosis. Duration of therapy in general should be around 12 months. Discontinuation of therapy should be considered if clinical remission lasts at least 6 months and the DIF test is negative. Recurrence of pruritus, blisters or erythemas may suggest relapse of BP.